O papel do terceiro setor nas políticas ambientais do estado neoliberal: uma análise a partir do Corede centro do Rio Grande do Sul - Dickel, Mara Eliana Graeff (2010)
The year of 1990 can be considered one in which the environmental issue reaches more visibility in the international arena and represents compulsory subject on the agenda. It s also during this period that, under hegemonic influence of neoliberal thinking in a context marked by the democratic restructuring, NGOs (Non Governmental Organizations) shall assume and create mechanisms for the management of "abandoned" territories by public institutions, starting to act in defense of the assumption of civil society participation in the state, assuming the role of public policies executors and supporting various forms of public services privatization, responding to the market demand. It is interesting to note that the emergence of ecological and environmentalists movements did not occur in a deserted political arena, its purposes are adding to the many social movements and popular causes that arise in response to the civilization model and exploratory force, acting as carriers of the constituent elements for the introduction of citizen's rights and citizenship. The main objective of this dissertation is to discuss the role of Non Governmental Organizations (NGOs) operating in the environmental limit of COREDE Centre of RS, based on the environmental policy of the Brazilian government after the 80's. The working sample consisted of active institutions (selected through the registration data provided by the Ministry of Justice) within the limits of COREDE Centre, considering only those who are dedicated specifically to environmental issues or working in related areas, totaling six institutions distributed among 19 counties in the Centre COREDE of the Rio Grande do Sul state. This research was based on a qualitative analysis methodology of managers and volunteers discourse analysis that belonged to the sample institutions. As a result, one can conclude that (a) the lack of a unified and updated database complicates the possibility of seeing in a clear way the relations between State and the third sector, also making harder the social control; (b) the institutions were not built through the process of social movements institutionalization; (c) mostly are functional to a corporate model consisting of neoliberal policies; (d) regarding the public policies, much of the sample was found to be consistent with the market precepts; (e) despite the environmental issue is not the central focus of many institutions, even if there were found three institutions that address this issue with actions that fill a critical and emancipatory educational practice.